Metabolism-independent phenomenon in ethanolic propolis inhibitory capacity towards enterococcus spp proteolytic activity - Adiningrat, Arya; Prabowo, Rizqi Alifna Waskita; Kurnia, Ridho; Septianti, Nurul Fitri Fika; Maulana, Ikhsan; Sofiani, Erma (Odonto : Dental Journal, 2022)
Background: Root canal bacteria produce many virulence factors which are responsible for endodontic pathological states. Bacteria are assumed to utilize energy from bacterial cell metabolism activity for producing these virulence factors. Propolis extracts are commonly reported to have antibacterial abilities against dental pathogens. The purpose of this study is to investigate the possible correlation between bacterial proteolytic and metabolism activities under the treatment of ethanolic extract of propolis (EEP).Method: The 0.00125%; 0.05%; 0.1%; 0.2%; 0.4%; and 0.8% ethanolic propolis were prepared for recovery rate confirmative procedure, proteolytic, and metabolism activity assay, with 2% of chlorhexidine gluconate (CHX) was used as a positive control. The bacteria were cultured in brain heart infusion (BHI) media after EEP treatment. Bacterial suspension was initially prepared in broth culture dilution with BHI media, followed by the gelatin liquefaction measurement for proteolytic assay. Phenol-red and arginine dehydrogenase enriched media for observing both carbohydrate and arginine metabolism activities, respectively, in the clinical Enterococcus spp. and E. faecalis ATCC 29212.Result: The recovery rate of the bacteria was not terminated after several EEP treatments. Proteolytic activity of the bacteria was likely decreased in several EEP treatments. EEP tended to affect the carbohydrate and arginine metabolism of the bacteria in certain fashions.Conclusion: This study suggested that the EEP treatment affected both proteolytic and metabolism activity in negative regulation tendencies.